Financial Literacy, Accounting Training, Motivation, Capital, Length of Business: MSME Success - Nawirah Nawirah; Ditya Permatasari; Devita Nur Romadhoni (Jurnal Akuntansi dan Perpajakan, 2023)
MSMEs play a crucial role in driving the national economy. However, many MSMEs in Indonesia lack an understanding of accounting practices and fail to apply accounting information effectively in recording financial reports for their businesses. To address this issue, one approach to increasing their knowledge is through enhancing financial literacy and participating in accounting training programs. This study aims to examine the impact of financial literacy, accounting training, motivation, capital, and business tenure on the success of MSMEs operating in the food and beverage sector in Probolinggo City. The research methodology employed a quantitative approach, utilizing purposive sampling with the Slovin formula to obtain a sample of 91 SMEs. Data gathered for the study were processed using validity and reliability tests conducted with the aid of the SmartPLS version 3 program. The research findings and analysis reveal that financial literacy, capital, and business tenure positively and significantly influence the success of MSMEs in the food and beverage industry. On the other hand, accounting training and motivation were found to have no significant impact on the success of MSMEs in the same industry in Probolinggo City.